2019
DOI: 10.25177/jeses.4.3.ra.507
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Sugar mill's Effluent on soil and Plant's Seed Germination, Punjab, Pakistan

Abstract: The present study was carried out to assess the physico-chemical analysis of sugar mill effluent and its impact on soil and seed germination of okra and tomato plants. Total 12 samples of sugar mill effluents were collected from different points. Similarly, 12 soil samples were collected from the fields irrigated with sugar mills effluents in radius of 500 meters and at a depth of 8 inches. All the analysis for both the effluents and soil were performed according to the Standard Methods. Mean values of the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Although the effects of industrial effluent are hazardous, Nath, Singh and Sharma (2007) found that it was occasionally used for irrigating numerous crops (wheat, garden pea, black gram, and mustard). Additionally, it was also observed that sugar factory effluent may be beneficial at 10% for Tagetes erecta L. (Thanapal and Perumal 2017); 40% for Zea mays L. (Vinod 2014); 40% for Raphanus sativus L. (Vijayaragavan et al 2011); 10% for okra and tomato plants (Musaa Khan, Yang and Din 2019). Moreover, they also found that sugar factory effluent is a good source of nutrition for vegetation if diluted before irrigation.…”
Section: Introductionmentioning
confidence: 97%
“…Although the effects of industrial effluent are hazardous, Nath, Singh and Sharma (2007) found that it was occasionally used for irrigating numerous crops (wheat, garden pea, black gram, and mustard). Additionally, it was also observed that sugar factory effluent may be beneficial at 10% for Tagetes erecta L. (Thanapal and Perumal 2017); 40% for Zea mays L. (Vinod 2014); 40% for Raphanus sativus L. (Vijayaragavan et al 2011); 10% for okra and tomato plants (Musaa Khan, Yang and Din 2019). Moreover, they also found that sugar factory effluent is a good source of nutrition for vegetation if diluted before irrigation.…”
Section: Introductionmentioning
confidence: 97%
“…Industrial effluents discharged into fresh water bodies can damage the quality of water, as they are known to contain excessive nutrients and toxins. India is witnessing a growing number of operational distilleries, numbering over 300, making it one of the largest agro-based polluting industries (Khan et. al., 2019 andKhalkar, 2021).…”
Section: Introductionmentioning
confidence: 99%